Nitrogen abundances in damped Lyman α systems: the combined effects of SNII and SNIa in a hierarchical clustering scenario - Tissera, Patricia Beatriz (2002)
The combined enrichment of supernovae (SN) types II and I in a hierarchical clustering scenario could produce regions with low N content with respect to α elements, consistent with observed values measured in damped Lyman α systems (DLAs). We have studied the formation of DLAs in a hierarchical clustering scenario under the hypothesis that the building blocks of current field galaxies could be part of the structures mapped by DLAs. In our models the effects of the non-linear evolution of the structure (which produces bursty star formation histories, gas infall, etc.) and the contributions of SNIa and SNII are found to be responsible of producing these N regions with respect to the α elements. Although SNIa are not main production sites for Si or O, because of the particular timing between SNIa and SNII, their contributions can help to produce clouds with such abundances. Consistently, we found the simulated low nitrogen DLAs to have subsolar [Fe/H]. We show that low nitrogen DLAs have experienced important star formation activity in the past with higher efficiency than normal DLAs. Our chemical model suggests that SNIa play a relevant role in the determination of the abundance pattern of DLA and, that the observed low nitrogen DLA frequency could be explained taking into account the time-delay of ≈0.5 Gyr introduced by these supernova to release metals.